The Effect of The Use of PGPR and NPK on The Vegetative and Generative Phases of The Marigold (Tagetes erecta L.): Pengaruh Penggunaan PGPR dan NPK Terhadap Fase Vegetatif dan Generatif Pada Tanaman Bunga Marigold (Tagetes erecta L.) - Achmad Fauzan; Sitawati, Sitawati (Jurusan Budidaya Pertanian Fakultas Pertanian Universitas Brawijaya, 2022)
Marigold plants are garden plants that are widely used in several regions in Indonesia due to their good adaptability. Chemical fertilizers produce residues that can later affect the chemical properties of the soil. Efforts to reduce the use of chemical fertilizers are by using organic fertilizers. The aim of the research was to study the interaction between the use of PGPR and NPK on the vegetative to generative phases of Marigold plants. The research was carried out from February 14 to May 12, 2022 at the Greenhouse of Brawijaya University, Jatimulyo Village, Lowokwaru District, Malang Raya, East Java. This study used a factorial randomized block design (RAK) with Factor I, namely four levels of PGPR concentration, including P0 = 0 ml l-1, P1 = 5 ml l-1, P2 = 10 ml l-1 and P3 = 15 ml l- 1. Factor II is three levels of NPK fertilizer doses, namely N0 = 0 g plant-1, N1 = 1.5 g plant-1 and N2 = 3 g plant-1. The materials used were 216 seeds of INCA Marigold plant seeds, raffia rope, stakes, alvaboard, water, NPK Mutiara (16:16:16), PGPR, and mixed planting media (soil: cocopeat: husk charcoal (1:1:1)). The results showed that there was an interaction between the concentration of PGPR and the dose of NPK on Marigold plant growth (total plant dry weight, top dry weight, and root dry weight). The total dry weight of Marigold plants at concentrations of PGPR up to 15 ml l-1 and NPK 3 g plant-1 increased by 23 times when compared to plants that were not given PGPR and NPK fertilizers. The use of NPK 2.42 g plant1 increased the number of Marigold flowers 10 times when compared to plants that did not use NPK fertilizer.